THE DEVELOPMENT OF MATHEMATIC ACHIEVEMENT ON STATISTICS USING INQUIRY CYCLE (5E INQUIRY BASED LEARNING) FOR MATHAYOMSUKSA 2 STUDENTS - Swangsri, Napatsorn; Varasunun, Pinda; Putjieb , Ratsaporn; Maneewong, Wattana (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of this research were 1) to develop a statistical learning method using the inquiry cycle (5E Inquiry-Based Learning) for Mathayomsuksa 2 students that meets the standard requirement of 70/70, 2) to compare the learning achievement in statistics of Mathayomsuksa 2 students before and after learning with the inquiry cycle (5E Inquiry-Based Learning) And 3) to study the satisfaction of Mathayomsuksa 2 students regarding statistics learning using the inquiry cycle (5E Inquiry-Based Learning). This research as one group pretest-posttest design. The sample group for this research consisted of 30 Mathayomsuksa 2 students from Bangplama “Soongsumarnpadungwit” School in the academic year 2023, selected through cluster random sampling. The research tools included lesson plans on statistics, a learning achievement test on statistics, and a satisfaction questionnaire related to the inquiry cycle (5E Inquiry-Based Learning). The statistical analyses used in this study were mean, standard deviation, percentage, and hypothesis testing, including the dependent t-test and one-sample t-test. The research results showed that 1) The lesson plans on statistics for Mathayomsuksa 2 students had a higher efficiency than the standard requirement of 70/70, with an E1/E2 score of 76.67/72.67. 2) The learning achievement in statistics of Mathayomsuksa 2 students after the trial was significantly higher than before the trial at the .01 level. 3) The overall satisfaction of Mathayomsuksa 2 students with statistics learning using the inquiry cycle (5E Inquiry-Based Learning) was at the high level.